Dynamic characteristics of negative stiffness structure with high static and low dynamic stiffness - Wang, Yuanshao; Zhang, Bao; Su, Xiaoping (Frontiers in Mechanical Engineering, 2025)
Negative stiffness (NS) structures have obvious advantages in attenuating low-frequency vibration. Although most existing NS structures exhibit good damping effects, their stability is poor, limiting their application in complex mechanical systems. To improve their damping and stability, a negative stiffness structure composed of rubber spring and elastic beam (NSS-RB) is proposed. Its elastic properties are studied via numerical modeling. Numerical and experimental results show NSS-RB has high static and low dynamic stiffness, achieving good damping and stability. Applied to a power battery package damping system, NSS-RB outperforms the rubber spring (RS) system in vibration reduction: the low-frequency vibration attenuation rate exceeds 90%, with good ride comfort and no instability.